Sensorineural Hearing Loss and Mitochondrial Apoptosis of Cochlear Spiral Ganglion Neurons in Fibroblast Growth Factor 13 Knockout Mice - Yu, Yulou; Yang, Jing; Luan, Feng; Gu, Guoqiang; Zhao, Ran; Wang, Qiong; Dong, Zishan; Tang, Junming; Wang, Wei; Sun, Jinpeng; Lv, Ping; Zhang, Hailin; et al. (Frontiers in Cellular Neuroscience, 2021)
Deafness is known to occur in more than 400 syndromes and accounts for almost 30% of hereditary hearing loss. The molecular mechanisms underlying such syndromic deafness remain unclear. Furthermore, deafness has been a common feature in patients with three main syndromes, the BÖrjeson-Forssman-Lehmann syndrome, Wildervanck syndrome, and Congenital Generalized Hirsutism, all of which are characterized by loss-of-function mutations in the Fgf13 gene. Whether the pathogenesis of deafness in these syndromes is associated with the Fgf13 mutation is not known. To elucidate its role in auditory function, we generated a mouse line with conditional knockout of the Fgf13 gene in the inner ear (Fgf13 cKO). FGF13 is expressed predominantly in the organ of Corti, spiral ganglion neurons (SGNs), stria vascularis, and the supporting cells. Conditional knockout of the gene in the inner ear led to sensorineural deafness with low amplitude and increased latency of wave I in the auditory brainstem response test but had a normal distortion product otoacoustic emission threshold. Fgf13 deficiency resulted in decreased SGN density from the apical to the basal region without significant morphological changes and those in the number of hair cells. TUNEL and caspase-3 immunocytochemistry assays showed that apoptotic cell death mediated the loss of SGNs. Further detection of apoptotic factors through qRT-PCR suggested the activation of the mitochondrial apoptotic pathway in SGNs. Together, this study reveals a novel role for Fgf13 in auditory function, and indicates that the gene could be a potential candidate for understanding deafness. These findings may provide new perspectives on the molecular mechanisms and novel therapeutic targets for treatment deafness.